Development of a methodological approach for processing different types of data in systems of special purpose - Fedoriienko, Vitalii; Koshlan, Oleksandr; Kravchenko, Serhii; Shyshatskyi, Andrii; Vasiukova, Nataliia; Trotsko, Oleksandr; Havryliuk, Oksana; Sovik, Oleksandr; Alieinik, Oleksandr; Svyryda, Yurii (Technology audit and production reserves, 2021)
The object of research is intelligent decision making support systems. Processing different types of intelligence from a variety of information sources requires significant computational operations with strict time constraints. It leads to the search for new scientific approaches to the processing of various types of geospatial information to increase the efficiency of special purpose systems. This work solves the problem of developing a methodological approach to processing different data types in decision making support systems. During the research, the authors used the main provisions of the queuing theory, the theory of automation, the theory of complex technical systems and general scientific methods of cognition, namely analysis and synthesis. The proposed methodological approach was developed taking into account the practical experience of the authors of this work during the military conflicts of the last decade. The results of the research will be useful in: – development of new algorithms for processing different types of data; – substantiation of recommendations for improving the efficiency of processing various data types; – analysis of the operational situation during the hostilities (operations); – creating promising technologies to increase the efficiency of processing various data types; – assessment of the adequacy, reliability, sensitivity of the scientific and methodological apparatus of processing various data types; – development of new and improvement of existing simulation models of various processing data types. Areas of further research will be aimed at developing a methodology for processing various data types in intelligent decision making support systems.